Convective Heat Transfer of Al2O3 and CuO Nanofluids Using Various Mixtures of Water-Ethylene Glycol as Base Fluids - Boukerma, K.; Kadja, M. (Engineering, Technology & Applied Science Research, 2017)
In this work, a numerical study has been performed on the convective heat transfer of Al2O3/Water-Ethylene Glycol (EG) and CuO/(W-EG) nanofluids flowing through a circular tube with circumferentially non-uniform heating (constant heat flux) under the laminar flow condition. We focus on the study of the effect of EG-water mixtures as base fluids with mass concentration ranging from 0% up to 100% ethylene glycol on forced convection. The effect on the flow and the convective heat transfer behavior of nanoparticle types, their volume fractions (φ=1-5%) and Reynolds number are also investigated. The results obtained show that the highest values of the average heat transfer coefficient is observed between 40% and 50% of EG concentration. The average Nusselt number increases with the increase in EG concentration in the base fluid, and the increase in the Reynolds number and volume fraction. For concentrations of EG above 60%, and for all volume fractions, the increase of thermal performance of nanofluids became inversely proportional to the increase of Reynolds number. In addition, CuO/(W-EG) nanofluids show the best thermal performance compared with Al2O3/ (W-EG) nanofluids.